2017
DOI: 10.1007/s10637-017-0470-z
|View full text |Cite
|
Sign up to set email alerts
|

Gilteritinib, a FLT3/AXL inhibitor, shows antileukemic activity in mouse models of FLT3 mutated acute myeloid leukemia

Abstract: SummaryAdvances in the understanding of the molecular basis for acute myeloid leukemia (AML) have generated new potential targets for treatment. Fms-like tyrosine kinase 3 (FLT3) is one of the most frequently mutated genes in AML and mutations in this gene are associated with poor overall survival. AXL plays a role in the activation of FLT3 and has been implicated in the pathogenesis of AML. The studies reported here evaluated the ability of a novel FLT3/AXL inhibitor, gilteritinib, to block mutated FLT3 in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(168 citation statements)
references
References 27 publications
6
155
0
Order By: Relevance
“…Despite these limitations, no significant differences in response rate, safety or PK profiles of gilteritinib were observed between our study and the phase 1/2 study . Furthermore, the demonstrated activity of gilteritinib against FLT3‐TKD mutations suggest a potential benefit in treatment‐resistant FLT3 mutation‐positive AML …”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Despite these limitations, no significant differences in response rate, safety or PK profiles of gilteritinib were observed between our study and the phase 1/2 study . Furthermore, the demonstrated activity of gilteritinib against FLT3‐TKD mutations suggest a potential benefit in treatment‐resistant FLT3 mutation‐positive AML …”
Section: Discussionmentioning
confidence: 68%
“…Gilteritinib is a highly specific, potent FLT3/AXL inhibitor with demonstrated activity against FLT3 receptors containing FLT3‐ITD and FLT3‐TKD D835 mutations . Preclinical studies have demonstrated that gilteritinib is a robust inhibitor of FLT3 and AXL, as well as anaplastic lymphoma kinase and leukocyte receptor tyrosine kinase .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations